Modelling the Water Sorption Isotherms of Quinoa Seeds (Chenopodium Quinoa Willd.) and Determination of Sorption Heats - Lemus-Mondaca, R (2012)
Adsorption and desorption isotherms of quinoa seeds (Chenopodium quinoa Willd.) were measured using the static gravimetric method at three temperatures (20, 40 and 60 °C). Water activity ranged from 0. 118 to 0. 937. The moisture sorption behaviour of quinoa was temperature dependent, as indicated by a decrease in equilibrium moisture content, at all levels of a w, with increasing temperature. Eight mathematical equations available in the literature were used to model the experimental data, namely, GAB, BET, Caurie, Henderson, Oswin, Halsey, Smith and Iglesias-Chirife. All the equations showed generally a good fit; however, the Iglesias-Chirife and Oswin equations were considered the best to predict the experimental data for both isotherms. Effect of temperature on model parameters was analysed and studied through an Arrhenius-type equation. The net isosteric heats of desorption and adsorption were determined by applying the Clausius-Clapeyron equation resulting in 69. 24 kJ mol -1 for desorption and 61. 26 kJ mol -1 for adsorption. The experimental heat data were satisfactorily modelled by Tsami s equation. © 2011 Springer Science + Business Media, LLC.